Efektivitas Penggunaan Media Gambar Dan Video Terhadap Hasil Belajar Seni Tari Di SMP Negeri 1 Batang Kapas - Vesilina Vesilina; Susmiarti Susmiarti (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
This study aims to identify and describe differences in the achievement of Dance learning among students at SMP Negeri 1 Batang Kapas, especially in the material of traditional Indonesian dance movements. This research uses a quantitative approach with Quasi-experiment method. The main instruments used to collect data were pretest and posttest. In this study, the population consisted of 174 students, with a sample consisting of class VII 3 as an experimental class that received treatment, and class VII 5 as a control class without treatment. The results of hypothesis testing showed that the use of images and video media had a significant impact on students' learning outcomes. With a significance level of 0.05, the calculated t value is -23.31, while the t table value is 1.669. Because t count is smaller than t table, it can be concluded that picture and video media are effective in improving students' learning outcomes.